2021
DOI: 10.1111/cid.13059
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of immediate implant placement in the anterior maxilla with dehiscence in the facial alveolar bone: A case series

Abstract: Background There is no clear evidence that immediate implant placement can be applied to cases with dehiscence in the facial alveolar bone prior to extraction. Purpose To evaluate the results of immediate implant placement in the anterior maxilla with facial alveolar bone dehiscence. Materials and Methods We super positioned pre‐ and post‐operative cone‐beam computed tomography (CBCT) three‐dimensional reconstruction images. A CBCT was taken before tooth extraction (T0), when the definitive restoration was pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In this study, the mid‐facial recession of implants at 1‐year was minimal (−0.03 ± 0.17 mm). This result was smaller compared to previous studies, where GBR using a flap‐involving approach was applied 10,11 . Mizuno and co‐workers reported that the mean change in vertical gingival recession measured on CBCT cross‐sections was 0.5 ± 0.5 mm.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…In this study, the mid‐facial recession of implants at 1‐year was minimal (−0.03 ± 0.17 mm). This result was smaller compared to previous studies, where GBR using a flap‐involving approach was applied 10,11 . Mizuno and co‐workers reported that the mean change in vertical gingival recession measured on CBCT cross‐sections was 0.5 ± 0.5 mm.…”
Section: Discussionmentioning
confidence: 62%
“…This result was smaller compared to previous studies, where GBR using a flap-involving approach was applied. 10,11 Mizuno and co-workers reported that the mean change in vertical gingival recession measured on CBCT cross-sections was 0.5 ± 0.5 mm. Another study by Liu and colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to previous literature, the causes of soft tissue retraction in this case can be attributed to the following: Firstly, the labial alveolar bone of the afflicted tooth exhibits a UU type bone defect. The research of Mizuno K established a notable positive correlation between alveolar bone defect severity and gingival recession ( 20 ). Additionally, the utilization of periodontal probes revealed the gums of patient to be of a thin gingival biotype ( 21 ), a significant risk factor for post-implant surgery gingival recession ( 22 ).…”
Section: Discussionmentioning
confidence: 99%